Gambaran Penjualan dan Investasi Obat Generik Apotek “X” Kelurahan Karang Anyar Kota Tarakan Menggunakan Analisis ABC Tahun 2022 - Ferry Fahruddin; Benazir Evita Rukaya; Syuhada Syuhada (Journal Borneo, 2024)
Pharmacies have a role in providing health services and as a business that follows the principle of profitability. If drug management is inefficient, it can result in excessive drug stocks and/or running out of stock of several types of drugs. This research aims to find out how big the percentage of drugs is in the number of sales transactions and the investment value in planning drug needs using the ABC analysis method at Pharmacy "X". This research is a retrospective study using quantitative descriptive methods. The object studied is data on the number of sales transactions for generic medicines at Pharmacy "X" for the period January-December 2022. The sample used in this study was 168 items of medicine sold throughout 2022 using a total sampling technique. The results of ABC analysis based on investment value show that group A consists of 34 medicinal items with an investment value of IDR 103,417,500 (69.43%), group B consists of 42 medicinal items with an investment value of IDR 30,276,000 (20 .33%) and group C consists of 92 items of medicine with an investment value of IDR 15,258,300 (10.24%). Group A drug items have the highest sales and investment levels, so it is important to ensure stock availability to reduce the risk of decreasing service quality and pharmacy losses.